Aggressive nutritional strategy in morbid obesity in clinical practice: Safety, feasibility, and effects on metabolic and haemodynamic risk factors. Issue 2 (March 2016) - Castaldo, Giuseppe; Palmieri, Vittorio; Galdo, Giovanna; Castaldo, Laura; Molettieri, Paola; Vitale, Assunta; Monaco, Luigi
Summary: Background: In morbid obesity, optimisation of nutritional strategies impacting cardiovascular and metabolic risk profile is a desirable target in clinical practice. Objective: To assess in morbid obesity the feasibility, safety and efficacy of a nutritional cycle comprising a short-term carbohydrates-free diet delivered by nasogastric tube followed by an almost equivalent oral diet. Design: In our clinical practice, adults with body mass index (BMI) ≥ 45 kg/m 2, otherwise clinically healthy, signed informed consent for a 14-day stint of continuous and controlled carbohydrates-free nutritional regiment delivered via 8-Fr nasogastric tube (enteral nutrition, EN), followed by a 14-day stint of almost comparable oral nutrition (ON). Body metrics, insulin resistance, blood pressure (BP) and heart rate (HR), as well as parameters for safety were monitored. Results: In 112 patients, EN significantly reduced BMI and waist circumference (WC), BP, insulin resistance while it increased urine ketones and uric acid increased (all p  < 0.01 independent to confounders), but had no clinically significant impact on kidney and renal function, and coagulation parameters as well. With ON, findings were consistent. No major safety concerns were recorded during the nutritional treatment. In a subset of patients sharing clinical characteristics with the whole sample, the nutritional strategy reduced the mesenteric fat assessed by ultrasound. Conclusions: In morbid obesity, an aggressive nutritional cycle comprising a short-term ketogenic EN followed by an almost carbohydrates-free ON may be feasible, safe, and highly effective in reducing body weight, WC, BP and insulin resistance.